The determinants of expatriate staffing by Japanese multinationals in Asia: control, learning and vertical business groups - Belderbos, René A; Heijltjes, Mariëlle G (Journal of International Business Studies, 2005)
We empirically examine the determinants of the decision whether or not to appoint an expatriate as the managing director of overseas affiliates for a sample of 844 Japanese manufacturing affiliates operating in Asia in 1995. Confirmation is found for hypotheses derived both from a control and coordination perspective on expatriation and from a knowledge creation and learning perspective. Strategic dependence of the parent on the affiliate increases the propensity to appoint expatriates, whereas localisation of the affiliate reduces it. Organisational experience in the country, both by the affiliate and by the firm, increases the probability that host country nationals will be appointed. Inter-firm relationships within vertical keiretsu groups impact on expatriation policies through inter-organisational knowledge exchange in host countries and the mitigation of localisation requirements owing to intra-group transactions.